2016
DOI: 10.17221/451/2015-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chestnut flour addition on quality characteristics of pasta made on extruder and minipress

Abstract: Kosović I., Jukić M., Jozinović A., Ačkar Đ., Koceva Komlenić D. (2016): Influence of chestnut flour addition on quality characteristics of pasta made on extruder and minipress. Czech J. Food Sci., 34: 166-172.Durum semolina was replaced with 10, 15, and 20% of chestnut flour. Pasta was produced on a single screw extruder with the temperature profile of 80/90/90°C and on a laboratory minipress. Pasta samples were dried at room temperature and physical and sensory properties were determined. Generally, the ches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
18
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 23 publications
6
18
2
Order By: Relevance
“…The maximum value of OCT (4.34 min) was obtained at BT= 105 ºC with N= 50 rpm. This value is less than the one mentioned by Kosović et al [25] and Manthey et al [22] (6.2 ± 0.1 and 10.2 min) for pasta made from durum semolina. On the other hand, Iancu et al [26] found OCT = 3 ± 0.5 min for GFP.…”
Section: Fig4 Effects Of Processing Variables On the Expansion Raticontrasting
confidence: 59%
See 1 more Smart Citation
“…The maximum value of OCT (4.34 min) was obtained at BT= 105 ºC with N= 50 rpm. This value is less than the one mentioned by Kosović et al [25] and Manthey et al [22] (6.2 ± 0.1 and 10.2 min) for pasta made from durum semolina. On the other hand, Iancu et al [26] found OCT = 3 ± 0.5 min for GFP.…”
Section: Fig4 Effects Of Processing Variables On the Expansion Raticontrasting
confidence: 59%
“…Generally, pasta made by extruder showed shorter OCT than other manufactures processing due to higher temperatures in the extrusion process and thus starch gelatinization [25]. The maximum value of OCT (4.34 min) was obtained at BT= 105 ºC with N= 50 rpm.…”
Section: Fig4 Effects Of Processing Variables On the Expansion Ratimentioning
confidence: 93%
“…In recent times, research has been focused on enrichment of extruded snacks with highly nutritious ingredients, such as protein and fiber, through the addition of vegetables, fruits, legumes, and food industry by‐products (Jozinović et al, ; Jozinović, Šubarić, Ačkar, Babić, & Miličević, ; Kosović, Jukić, Jozinović, Ačkar, & Koceva Komlenić, ; Larrea, Chang, & Martinez‐Bustos, ; Obradović, Babić, Šubarić, Jozinović, & Ačkar, ; Obradović et al, ; Panak Balentić et al, , ; Stojceska, Ainsworth, Plunkett, Ibanoglu, & Ibanoglu, ;Stojceska, Ainsworth, Plunkett, & Ibanoglu, ; Stojceska, Ainsworth, & Plunkett, ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the nutritional advantages, chestnut is a gluten-free fruit and therefore suitable for people suffering gluten-related disorders such as celiac disease, which treatment relies on absolute and lifelong dietary withdrawal of gluten [8]. Indeed, in the last years several works have reported the use of chestnut flour in the manufacture of gluten-free and functional food products, such as, bread, cookies, muffins, pasta, snacks and probiotic fermented milk supplemented with chestnut flour [7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. In fact, since most of the gluten-free cereal products contain low amounts of health beneficial components, it may be advantageous to use chestnut flour due to its nutritional value [23].…”
Section: Introductionmentioning
confidence: 99%